2017
DOI: 10.1016/j.jns.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A two-year study using cerebral gray matter volume to assess the response to fingolimod therapy in multiple sclerosis

Abstract: These results suggest a treatment effect of fingolimod on cerebral GM atrophy in the first two years. GM atrophy is more sensitive to such effects than whole brain atrophy. However, due to the non-randomized, retrospective design, heterogeneous between-group characteristics, and small sample size, these results require confirmation in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 108 publications
(195 reference statements)
3
19
0
Order By: Relevance
“…However, no similar effects were reproduced in patients with the primary progressive form of MS, a finding that that could have otherwise strengthened the evidence for a direct action of fingolimod on brain cellular components [126]. Finally, further condoning the aforementioned observations, in a study by Yousuf et al [127], cortical GM, alongside T2 lesion volume, remained stable in the cohort treated with fingolimod, as compared to the untreated group, where it decreased and increased respectively, in the first 2 years of treatment.…”
Section: Rrmsmentioning
confidence: 94%
“…However, no similar effects were reproduced in patients with the primary progressive form of MS, a finding that that could have otherwise strengthened the evidence for a direct action of fingolimod on brain cellular components [126]. Finally, further condoning the aforementioned observations, in a study by Yousuf et al [127], cortical GM, alongside T2 lesion volume, remained stable in the cohort treated with fingolimod, as compared to the untreated group, where it decreased and increased respectively, in the first 2 years of treatment.…”
Section: Rrmsmentioning
confidence: 94%
“…Brain parenchymal fraction (BPF) and cortical gray matter fraction (cGMF) were evaluated after 2 years of FTY720 administration in MS patients. BPF did not change, but cGMF was stable in FTY720-treated group in contrast to its increase in the control group, indicating that FTY720 has a preservative impact in the CNS tissue of MS patients (Cohen & Chun, 2011;Yousuf et al, 2017). Assessment of FTY720 efficiency in INFORM trial (a phase 3, multicenter, double-blind, placebo-controlled parallelgroup study) in primary progressive MS patients showed no reduction in clinical features and failed to prevent brain loss volume (Ciotti & Cross, 2018;Lublin et al, 2016).…”
Section: E Viden Ce For Protec Tive/ Reg Ener Ative Effec Ts Of F Tmentioning
confidence: 99%
“…The BVI of mild multiple sclerosis patients tended to decrease with age at the same rate as that of the control participants. 2 Another limitation of the present study was that, in contrast to a previous report, 13 we could not investigate the decrease rates of GM or WM volumes compared with those of controls. Figure 6 The brain volume index (BVI) of secondary progressive multiple sclerosis patients.…”
Section: Discussionmentioning
confidence: 66%
“…There is another report about brain shrinkage in aging from the same research group, but the authors did not discuss the shrinkage rate, and compared individuals aged in their 20s with individuals aged >65 years. 2 Another limitation of the present study was that, in contrast to a previous report, 13 we could not investigate the decrease rates of GM or WM volumes compared with those of controls. Therefore, further investigation is required.…”
Section: Figurementioning
confidence: 66%